Perception about Health and Disease - Syed Arshad Sabir; Nadeem Ikram (Journal of Rawalpindi Medical College, 2009)
Background: To assess peoples’ general concepts about health and disease and basis of disease occurrence in man in an objective way. Methods: It was an observational descriptive study. Perceptions of the attendants (n=110) of the patients who approached a public sector tertiary care hospital in Rawalpindi were assessed through a questionnaire by interviewer-administered technique. Their concepts about health and disease were explored by open-ended questions and their understanding of ways of disease causation evaluated six sets of closed ended options. Results: Of the total study participants (n=110), with mean age 36 Years, 58% were males and 42% were females. Majority were married (71%) , of lower economic status (45%), and rural area (70%). Education in 51% was above 10years of schooling. In 36% subjects concept of health and in 25% concept of disease was scientifically appropriate at their level. On average 66.3% of the respondents had concept of scientific basis of disease. causation while 33.6% did not hold scientifically sound concepts. In set-IV majority believed in that disease may result as punishment from God but this belief was significantly high in females (X2cal= 8.1, P<0.005). Conclusion: Though people understandings in matter of health are not optimum but it is promising within their socioeconomic capacity. Efforts are needed to promote health literacy among masses beyond the conventional mode. Care providers should respect their beliefs while interacting with patients.